The Importance Of Pros For English Learning In Elementary School - Puspitasari, Devita Indah; Azhar, Farid Syahrul; Khasanah, Intan Aminatul (Prosiding University Research Colloquium, 2021)
The purpose of this activity is to determine the effect of learning media or teaching aids inlearning English in elementary schools. This study uses classroom action research, in thisstudy we get data that many elementary school students still have difficulty in learningEnglish. Can increase the focus of learning on students and make students moreenthusiastic about learning. Through flash card learning media, it can improve skills inreading the alphabet and also vocabulary. According to the data we took form severalreferences, one of wich was in MI-Ar Rohman Semarang successfully implemented Englishlearning through flashcard learning media successfully and students could easily learnEnglish. Learned and can increase students’ learning motivation.